Comparison of Muscle Mass, Total Body Water and Total Body Protein in Type II Diabetics with Healthy Matched Adults by Bioelectrical Impedance Analysis - Parsa Jahanlou (Shahid Sadoughi University of Medical Sciences and Health Services, 2021)
Background: Bioelectrical impedance analysis (BIA) is a new and rapid technique to validate body composition. Several studies have used this technique to evaluate body compositions, such as muscle mass, in diabetic patients, but the results are very different. This may due the differences between diabetic patients and control group. Therefore, this study aimed to compare the muscle mass of diabetic patients with healthy matched adults using the BIA method. Methods: This descriptive cross-sectional study was conducted on 928 diabetic patients and 928 healthy individuals selected based on gender, age, height, weight, and closeness to demographic conditions. Body composition was measured by the BIA technique. Total body water, muscle mass in the trunk, legs, hands, and total body protein were measured by this method. The data were analyzed using t-test, paired t-test, and one-way ANOVA. Results: Diabetic women aged 50-60 years showed that their body weight, total protein, total muscle, right-hand muscle mass, left-hand muscle mass, right foot muscle mass, left foot muscle mass, and trunk muscle mass were higher than healthy matched women, and the differences were significant. Conclusion: Diabetic women aged 50-60 years showed the most significant difference compared to other age groups. It seems that diabetes along with the changes in humeral status in this age group due to menopause affected their body weight, total muscle mass, hand and leg muscles, and trunk muscles mass, and total body protein compared to healthy matched women. However, diabetic men showed no significant difference in the studied variables compared to healthy male subjects.